What is the value of n? 9×27+2×31-28=n

Answers

Answer 1
Answer: So,

9*27 + 2*31 - 28 = n

We use PEMDAS.

Multiply from left to right.
243 + 2*31 - 28 = n
243 + 62 - 28 = n

Add or subtract from left to right.
305 - 28 = n
277 = n

Related Questions

If someone eats 3 sundaes in 9 minutes what portion of a sundae can they eat in one minute
Lynn bought a bag of grapefruit 1 5/8 pounds of apples to + 3/16 pounds of bananas the total weight of her purchase with 7 1/2 pounds how much did the bag of grapefruit way
WHAT capital letter forms a parallel lines
Find the 15th term in the Arithmetic Sequence An = 3n-7 Question 1 options: a32 b 7 c 38 d -2 please help
28 inches to 3 feet ratio​

What are the solutions(s) to the quadratic equation 40 - x2 = 0?

Answers

Divide 40 and 20 by 2, the 2 cancels out, bring down the variable, 20= 0
\bf 40-x^2=0\implies 40=x^2\implies \pm√(40)=x\n\n\n\pm√(2^2\cdot 10)=x \implies \pm 2√(10)=x

Bashar went bowling with $25 to spend. He rented shoes for $5.25 and paid $4.00 for each game. What was the greatest number of games Bashar could have played?

Answers

you would subtract the bowling shoes from 25 and then subtract what ever is left as many times as u can by 4 and u will get ur answer..... 4 games

\$25-\$5.25=\$19.75

\$19.75:\$4.00\approx 4.9

Max. 4 games.

(5+10p) +13
a.28p
b.15p+13
c.23p+5
d.10p+18

Answers

5+10p+13 <--remove the parentheses  
And now just add like terms
(10p)+(5+13)
10p+18 <---answer
Now, here, we need to combine like terms.

5 and 13 are like terms.

5+13 = 18

Final answer:  10p + 18

Rewrite by completing the square. 2x^2+7x+6=0

Answers

(2x + a)(x + b)

2b + a = 7
b*a = 6

factors of 6: (2x3) and (6x1)

let b = 2, a = 3

2(2)+ 3 = 7 check

(2x + 3)(x + 2)

Final answer:

To complete the square and rewrite the quadratic equation 2x^2+7x+6=0, follow these steps: move the constant term, divide the coefficient of x^2, square half of the coefficient of x, add the result to both sides, factor the left side, take the square root, and solve for x.

Explanation:

To rewrite the quadratic equation 2x^2+7x+6=0 by completing the square, follow these steps:

  1. Move the constant term to the other side of the equation: 2x^2+7x = -6.
  2. Divide the coefficient of x^2 by 2: x^2+(7/2)x = -3.
  3. Take half of the coefficient of x and square it: (7/4)^2 = 49/16.
  4. Add the result from step 3 to both sides of the equation: x^2+(7/2)x+49/16 = -3+49/16.
  5. Factor the left side of the equation: (x+7/4)^2 = (1/16).
  6. Take the square root of both sides of the equation: x+7/4 = ±(1/4).
  7. Solve for x: x = -7/4 ±(1/4).

Learn more about quadratic equations here:

brainly.com/question/30098550

#SPJ12

Agent Hunt is transferring classified files from the CIA mainframe to his flash drive. The variable S models the size of the files on the drive (in megabytes) after t seconds of transfer. S=5t+45 How many megabytes does Agent Hunt transfer every 10 seconds?

Answers

Answer:

50MB

Step-by-step explanation:

\bold{METHOD\ 1:}\n\n\text{Calculate the value of }S\ \text{in}\ 10s,\ 20s,\ 30s,\ ... \text{and difference if them}\n\nfor\ t=10:\n\nS=5(10)+45=50+45=95\n\nfor\ t=20:\n\nS=5(20)+45=100+45=145\n\nfor\ t=30:\n\nS=5(30)+45=150+45=195\n\n195-145=50\n145-95=50\n\n\boxed{50\ MB\ per\ 10s}

\bold{METHOD\ 2:}\n\nS_1=5t+45\to \text{in t second}\n\nS_2=5(t+10)+45\to \text{10 second leter}\n\n\text{Difference}\n\nS_2-S_1=5(t+10)+45-(5t+45)=5t+50+45-5t-45=50\n\n\boxed{50MB\ per\ 10s}

Answer:

50MB (MEGABITES)

Just rationalize and simplify

Answers

\mathsf{Given :\;\;(√(a + 1) - 2)/(√(a + 1) + 2)}

\mathsf{Multiplying\;Numerator\;and\;Denominator\;with\;√(a + 1) - 2,\;We\;get :}

\mathsf{\implies ((√(a + 1) - 2)(√(a + 1) - 2))/((√(a + 1) + 2)(√(a + 1) - 2))}}

\mathsf{\implies ((√(a + 1) - 2)^2)/((√(a + 1))^2 - (2)^2)}}

\mathsf{\implies ((√(a + 1))^2 + (2)^2 - 2(√(a + 1))(2))/(a + 1 - 4)}}

\mathsf{\implies (a + 1 + 4 - 4√(a + 1))/(a + 1 - 4)}}

\mathsf{\implies (a + 5 - 4√(a + 1))/(a - 3)}}

Answer:

(a+5)-4√(a+1) /(a-3)

Step-by-step explanation:

√(a+1) - 2 / √(a+1) + 2

={√(a+1) - 2 }{√{(a+1) - 2 }  / {√(a+1) + 2} {√(a+1) - 2 }

={√(a+1) - 2 }² / {√(a+1)}² - 2²

=[ {√(a+1)}² -4√(a+1) +4 ] / a+1-4

=[a+1-4√(a+1)+4] / (a-3)

=(a+5)-4√(a+1) /(a-3)